Atomic-scale segregations at the deformation-induced symmetrical boundary in an Mg-Zn-Y alloy. (1st October 2016) - Shao, X.H.; Peng, Z.Z.; Jin, Q.Q.; Ma, X.L.
Abstract: Solute atoms segregation to the interfaces, such as grain boundary or twin boundary, often plays a critical role in modulating the properties of a metallic alloy. Deformation induced segregation to the interfaces has been a subject of significant research, since this is one of the key issues to fully understand the deformation mechanism and microstructure evolution in service of engineering materials. By means of the high-resolution aberration-corrected scanning transmission electron microscopy (STEM), we report the investigations of segregations to symmetrical boundaries, kink boundary (KB) and twin boundary (TB), in the Mg-Zn-Y alloys containing long period stacking ordered (LPSO) phases subjected to a compression at room temperature. We found that Zn atoms preferentially segregate to the deformation-induced symmetrical KBs in the LPSO structures and sandwiched Mg layers, while only a small amount of Y atoms concentrate at KB in LPSO structure. These enriched atoms may be in a random distribution, form nanoscale clusters or in a periodic pattern. Furthermore, solute atoms would rather decorate the segment of coherent TBs than enrich the overlapped TBs. Based on the direct atomic observations, the segregation mechanisms to the featured microstructures are proposed. Graphical abstract: